IMPLEMENTASI MEDIASI PENAL SEBAGAI PERWUJUDAN NILAINILAI PANCASILA GUNA MENDUKUNG SUPREMASI HUKUM DALAM RANGKA PEMBANGUNAN NASIONAL - Yusriando Yusriando (Jurnal Pembaharuan Hukum, 2015)
Implementation of Penal Law Mediation important existence out of court settlement to the case. The substance of penal mediation was born, grow, develop and earth excavated fromIndonesia through the local wisdom of indigenous (local wisdom) and the values   of Pancasila. In Indonesia, the national perspective penal mediation is set in a limited and partial in theRegulations and the Letter of the Chief of Police and regulation. From the persp e ctive of practice, penal mediation is done through the discretion of law enforcement officials, customaryjustice, the jurisprudence of the Supreme Court and the District Court’s decisi o n. Necessary to optimize the application of the values   of Pancasila in the law because it values   the life as a whole contained in the principles of Pancasila. If this is done, the law in question is relatively acceptable because people assume that the law reflects the values   of justice, rule of law, orderand contain the benefits to society so as t o support the rule of l aw in the context of  national development.